HEMODYNAMICS FOR ASYMMETRIC INLET AXIAL VELOCITY PROFILE IN CAROTID BIFURCATION MODEL - DING, Zu-rong; LIU, Bin; YANG, Shuo; XIA, Yan (Journal of Hydrodynamics, 2008)
The asymmetric inlet velocity profile has been observed in phantom model using LDA and in health subjects using Magnet Resonance （MR）. The effects of asymmetric inlet axial velocity profile on the flow field and the Wall Shear Stress （WSS） of carotid bifurcation were numerically studied herein with the TF-AHCB model, The results show that the Wall Shear Stress Gradient （WSSG） in the front part of the sinus for inward-tilting inlet axial velocity profile is nearly 2 times of that for the symmetric one in the beginning of systole, the end of systole, and diastole, respectively. The area of WSS below 5× 10^-3 Pa at the outer wall of the sinus for outward-tilting inlet axial velocity profile is 1.5 times of that for the inward-tilting one during diastole of the cardiac cycle. The asymmetric inlet velocity profiles can reduce the flow velocity near the inner wall of the sinus, which has been normally considered a high velocity region. It is concluded that besides bifurcation geometry and flow waveform, the asymmetry of inlet velocity profile is probably a factor influencing atherosclerosis.